2017
DOI: 10.3892/mmr.2017.8245
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 2 is involved in �‑opioid receptor suppression in the spinal dorsal horn in a rat model of chronic pancreatitis pain

Abstract: Chronic pain occurs in ~85–90% of chronic pancreatitis (CP) patients. However, as the pathogenesis of CP pain remains to be fully understood, the current therapies for CP pain remain inadequate. Emerging evidence has suggested that the epigenetic modulations of genes are involved in chronic pain. In the present study, intrapancreatic trinitrobenzene sulfonic acid infusions were used to establish a CP model in rats. Mechanical allodynia was measured with von Frey filaments. Immunofluorescent staining analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 41 publications
5
12
0
Order By: Relevance
“…We also found that SAHA administration could not affect basal HDACs of the Sham group ( Fig. 6c-e), which agreed with previously published researches [48]. Other studies have also indicated that SAHA can selectively alters the transcription of relatively few genes, and normal cells are at least ten fold more resistant than transformed cells to SAHA and related HDAC inhibitor-induced cell death (for example, see [49]).…”
Section: Discussionsupporting
confidence: 92%
“…We also found that SAHA administration could not affect basal HDACs of the Sham group ( Fig. 6c-e), which agreed with previously published researches [48]. Other studies have also indicated that SAHA can selectively alters the transcription of relatively few genes, and normal cells are at least ten fold more resistant than transformed cells to SAHA and related HDAC inhibitor-induced cell death (for example, see [49]).…”
Section: Discussionsupporting
confidence: 92%
“…The different effects of SAHA on opioid-induced pain behavior might be due to different pathological conditions. Liang et al studied the effects of SAHA on morphine-induced hyperalgesia in normal conditions ( Liang et al, 2013 ), while our study and those by other researchers examined the effects of SAHA on morphine tolerance in the pathogenesis of chronic pain ( Hou et al, 2017 ; Liao et al, 2018 ). HDAC expression and histone acetylation in pathological conditions may be quite different from those in physiological conditions.…”
Section: Discussionmentioning
confidence: 83%
“…The effects of HDACi on morphine tolerance are controversial. Some studies have indicated that HDACi can enhance the analgesic effects of morphine and attenuate morphine tolerance ( Dobashi et al, 2010 ; Tsai et al, 2016 ; Hou et al, 2017 ; Liao et al, 2018 ). However, some studies have demonstrated that chronic morphine treatment with simultaneous SAHA treatment can enhance opioid-induced hyperalgesia ( Liang et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Though controversies still exist, upregulated HDACs and resultant downregulation of histone acetylation were believed to facilitate pathological pain and opioid-insensitive status in the majority of studies (Uchida et al, 2010; Denk et al, 2013; Matsushita et al, 2013; Cherng et al, 2014). Accordingly, several kinds of HDAC inhibitors, including TSA, SAHA, sodium butyrate, MS-275, and LG325 exert analgesic effects in multiple pain models (Agudelo et al, 2011; Denk et al, 2013; Kukkar et al, 2014; Hou et al, 2017; Sanna et al, 2017; Danaher et al, 2018; Liao et al, 2018; Sanna and Galeotti, 2018; Zhao and Wu, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that chronic fluoxetine treatment induced a sex-dependent analgesic effect, and this phenomenon may be mediated by HDAC2 repression and incremental mGlu2 receptor expression in the spinal cord dorsal horn of female mice (Zammataro et al, 2017). Recently, participation of HDAC2 in bone cancer pain and chronic pancreatitis pain was proposed, as a favorable pain-relieving effect was observed after HDAC2 knockdown or inhibition (Hu et al, 2017; Hou et al, 2018; Liao et al, 2018). In the present study, we found that HDAC2 mRNA and protein levels were both elevated after sciatic nerve constriction.…”
Section: Discussionmentioning
confidence: 99%